Study of Protection Structures Planning for Krui Beach, Pesisir Barat Regency, Lampung Province - Nanda Nurisman; Trika Agnestasia Tarigan (Journal of Science and Applicative Technology, 2019)
Labuhan Jukung Beach is one of the beaches in Kru, which is located on Krui Bay, West Coast District. This beach is a tourist beach directly adjacent to the Indian Ocean, so it has a high wave. Based on wind data from 2008 – 2017 that be analyzed in this research, Krui Beach has extreme wave height (25th return period) as big as 6 meters in deep-sea water and 3.4m in shallow water, consequently Krui Beach has the potential to erode To resolve these problems, must be built environmentally friendly coastal protection structure. The structure that can be used in this beach is groynes. Groynes serve as sediment traps and existence of groin does not disturb tourists who surf the beach. Based on HWS value and run-up wave calculation, the groin structure need to has elevation +10.3m from seabed, with armor weight is 6.3 ton.